The Effect Of Work Experience, Organizational Citizenship Behavior (OCB), Commitment Towards Employee Performance At PT. Pelabuhan Indonesia (Persero) Regional I - Vadiah Sahnanda Putri; Santi Rizki (Green Inflation: International Journal of Management and Strategic Business Leadership, 2024)
Employee performance is one of the important factors that must be prioritized in order to be able to face and win competition at both national and global levels. The full performance of workers in carrying out their duties, whether an employee's performance is good or bad, is determined by their performance. This research aims to determine the influence of work experience, organizational citizenship behavior (OCB), commitment on employee performance at PT. Pelabuhan Indonesia (Persero) Regional I. The method in this research is the Quantitative Method, the number of samples for this research is 110 respondents. Data collection techniques in this research are questionnaires, observation, pre-survey interviews, data analysis using multiple linear regression tests and descriptive statistics. Data management in this research uses SPSS 25 for Windows. Based on the research results, it shows that work experience has a positive and significant effect on employee performance with a significant value of 0.039, organizational citizenship behavior (OCB) has a positive and significant effect on employee performance with a significant value of 0.040, and commitment has a positive and significant effect on performance with a significant value. of 0.001. work experience, organizational citizenship behavior (OCB) and commitment simultaneously influence work productivity in PT, Pelabuhan Indonesia (Persero) Regional I employees with a sig value of 0.000.